Peran Inovasi dalam Pengembangan Model Bisnis UMKM di Era Digital - Putri, Puspita Lianti; Widadi, Budi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The digital era has brought significant changes to various aspects of life, including the business world. Information and Communication Technology (ICT) offers new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to innovate and enhance their competitiveness through various aspects such as products, processes, and business models. MSMEs play a crucial role in the Indonesian economy, contributing approximately 60% to Gross Domestic Product (GDP) and absorbing over 97% of the workforce. Despite this, MSMEs often face challenges such as limitations in capital, technology, and market access. Digital transformation presents great potential to address these challenges by improving operational efficiency, expanding market reach, and developing more relevant products and services. Business model innovation, which involves the use of digital technology to create effective solutions, can enhance MSME performance, as demonstrated by previous research. However, barriers such as limited resources and digital skills often hinder technology adoption. This research aims to examine the role of innovation in the development of MSME business models in the digital era, focusing on the utilization of digital technology, success factors of innovation, and impacts on business performance. Additionally, the study will explore strategies to overcome obstacles in the innovation process. The research is expected to provide in-depth insights and practical recommendations for MSMEs in developing innovative and sustainable business models in the digital era.